HAMBATAN GURU DALAM MENINGKATKAN HASIL BELAJAR SISWA DI SDN 9 MAMBORO - Sutriani, Komang; Hariani, Ni Made Mega; Putrayasa, I Wayan Budiagus (JATMIKA : Journal Education and Learning of Elementary School, 2024)
This research aims to determine teachers' obstacles as well as ways to overcome and supporting factors for teachers to improve student learning outcomes at SDN 9 Mamboro. The method used is qualitative research in the form of descriptive data using three data collection techniques consisting of: observation, interviews and documentation. The technique for determining informants in this research uses a purposive sampling technique. The results of the research show that there are obstacles experienced by teachers in improving the learning outcomes of lower class students, namely: low student ability in calistung, students playing more than studying, students making more noise when studying. And high class, namely: lack of understanding of the material provided by the teacher, students' different grasping abilities, difficulty in using IT technology and the teacher cannot convey the material in full. The ways teachers overcome obstacles in improving the learning outcomes of lower class students are: approaching students, providing stimulus in calistung, inviting students to sing, forming student study groups. And high class, namely: observing students, the teacher guiding the students one by one, and providing motivation.